1999
DOI: 10.1017/s1355838299981803
|View full text |Cite
|
Sign up to set email alerts
|

Finding the right RNA: Identification of cellular mRNA substrates for RNA-binding proteins

Abstract: Defects in RNA-binding proteins have been implicated in human genetic disorders. However, efforts in understanding the functions of these proteins have been hampered by the inability to obtain their mRNA substrates. To identify cognate cellular mRNAs associated with an RNA-binding protein, we devised a strategy termed isolation of specific nucleic acids associated with proteins (SNAAP). The SNAAP technique allows isolation and subsequent identification of these mRNAs. To assess the validity of this approach, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…The K562 cell line was chosen for this analysis. This human erythroid cell line contains high levels of human ␣-globin and ␥-globin mRNAs which can serve as positive and negative controls, respectively, for the IP reaction; interaction of ␣-globin mRNA with ␣CP2 has been previously characterized in detail and has a defined biologic function (23), while ␥-globin mRNA lacks ␣CP binding sites (49). Native ␣CP2-RNP complexes were immunoprecipitated from K562 cytoplasmic extracts using an affinity-purified rabbit antiserum specific to the two predominant human ␣CP isoforms, ␣CP2 and ␣CP2-KL (anti-␣CP2) (6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The K562 cell line was chosen for this analysis. This human erythroid cell line contains high levels of human ␣-globin and ␥-globin mRNAs which can serve as positive and negative controls, respectively, for the IP reaction; interaction of ␣-globin mRNA with ␣CP2 has been previously characterized in detail and has a defined biologic function (23), while ␥-globin mRNA lacks ␣CP binding sites (49). Native ␣CP2-RNP complexes were immunoprecipitated from K562 cytoplasmic extracts using an affinity-purified rabbit antiserum specific to the two predominant human ␣CP isoforms, ␣CP2 and ␣CP2-KL (anti-␣CP2) (6).…”
Section: Resultsmentioning
confidence: 99%
“…4E). Even though it is not present on the microarray used in these studies, we wanted to assess whether this mRNA interacts with ␣CP2 because it has been shown previously to be a binding partner of ␣CP1 (49). Figure 4E shows that coxII mRNA is robustly associated with ␣CP2-RNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the target mRNAs of many RBPs have not been identified and different RBPs may bind the same target http://bmbreports.org BMB reports mRNAs, GST protein was used as a control. In order to provide the natural circumstances of competitor proteins and increase the binding specificity of the protein-mRNA, the total embryo extract was chosen to enable the identification of true mRNA substrates (12). As a result, 13 target mRNAs were bound by GST-ZDnd protein (Table 1).…”
Section: Identification Of the Target Mrnas Of Zdnd Protein By Sannp mentioning
confidence: 99%
“…This assay adopts copurification of unknown mRNAs bound by an RNA-binding protein and subsequently isolates the mRNAs using differential display technology [18]. We herein report the testis-specific substrate mRNAs bound by hRBMY.…”
mentioning
confidence: 99%